Capacidad productiva de pastizales bajo plantaciones de distinta densidad de Eucalyptus globulus en el sudeste bonaerense - Quiñones Martorello, Adriana Silvia (2023)
Forage production in silvopastoral systems depends mainly on the level of radiation that reaches the herbaceous stratum and the ability of species to fix carbon (C) in their biomass and, at the same time, to respond positively to grazing. Thus, in the Estación Experimental Agropecuaria Balcarce, a factorial test of solar radiation (3 levels) x cut (3 levels) was proposed in Eucalyptus globulus plantations in order to have information that allows the development of management standards for silvopastoral systems based on forage production. The plots with the highest tree density showed individuals with a smaller diameter and a greater crown cover, intercepting 90% of the photosynthetically active radiation. The annual productivity was different according to the degree of solar radiation and cutting frequency, being higher in the grassland (305 gr dry matter (DM) m-2) than in high tree density (115 gr DM m-2) and in the low frequency treatment cutting (289 gr DM m-2) than in the situation without cutting (94 gr DM m-2). The forage productivity peak was observed in autumn, showing a relatively constant rate of production during the summer. The variation in the water content in the soil appears as a variable that could also limit forage production in synergy with the lack of solar radiation. Despite the fact that forage productivity was relatively high even with low radiation levels, these results show the need to manage forest cover to avoid depressing production.